Successful Retrieval of Rota Burr After Driveshaft Fracture - Tsuyoshi Kobayashi; Takeo Horikoshi; Toru Yoshizaki; Akira Sato (Case Reports in Cardiology)
Rotational atherectomy is an effective procedure for heavily calcified lesions and those that cannot be crossed using conventional percutaneous coronary intervention (PCI) devices. Here, we report a rare case of intracoronary burr entrapment in the coronary artery due to burr disconnection from the driveshaft. A 67-year-old man undergoing hemodialysis for nephrosclerosis presented with exertional chest discomfort. Coronary angiography revealed stenotic lesions in the right coronary artery, and PCI was performed using a Rotawire Floppy. During the procedure, the disconnected burr was successfully removed without surgery using the child-in-mother technique with a guide extension catheter. Notably, the patient remained hemodynamically stable throughout the procedure and his recovery was uncomplicated. He was discharged on the second postprocedural day. At the 6-month follow-up, the patient remained asymptomatic with no evidence of myocardial ischemia. This report informs clinicians of the possibility of burr disconnection and the non-surgical intervention used for its removal.